PKM Pembuatan “CAPCIN WARTH” Bagi Masyarakat di Kecamatan Rappocini - Ratnah S; Nurjannah Nurjannah; Mustari Mustari; Nur Arisah; Sitti Hajerah Hasyim (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The Capocino Cincau product is one of the innovations in the beverage industry that combines the deliciousness of cappuccino with the pleasure and benefits of cincau. This community service aims to increase the income value of the community by innovating one of the drinks, namely Capocino Cincau, into an attractive drink with an affordable price, namely "CAPCIN WARTH". The methods used in this activity include lectures, questions and answers or discussions, and training. The results obtained are (1) Training and mentoring in making "CAPCIN WARTH" were responded well by the participants; (2) The high interest and motivation of the training participants greatly support the transfer of knowledge and skills from the community service to the training participants, so that the training materials provided can be absorbed by all; and (3) The training product for making "CAPCIN WARTH" can be consumed daily and can be used as an entrepreneurial product.